Intiḵẖāb-i yādgār - Amīr Mīnāʼī, Amīr Aḥmad, 1828-1900 (Silsilah-yi ma̤tbūʻāt (Uttar Pradesh Urdū Akāḍmī), 1982)
Biographical dictionary of early Urdu poets, most from the court of Rampur, former Indian princely state; includes a sampling of their poems.